Bochdalek hernia in adults: A case report - Ivošević Anita; Meta-Jevtović Ivana; Ćupurdija Vojislav; Čekerevac Ivan; Radunović Aleksandar; Jovanović Milan; Vulović Maja; Spasić Marko; Petrović Marina (Vojnosanitetski Pregled)
Introduction. Asymptomatic Bochdalek hernia in adults is a rarity. The aim of this paper is to present a rare case of Bochdalek hernia among adults and to point out to significance of clinical suspicion and important role of imaging techniques in reaching the exact diagnosis of this abnormality. Case report. A patient, aged 68 years, came to the Clinic of Pulmonology complaining of constant dyspnea, coughing and fatigue. Computed tomography (CT) findings were dominated by the large rear right diaphragmatic hernia with the hernial sac that reached the carina trachea and urged the principal bronchi. The stomach, duodenum and proximal part of jejunal winds, as well as a greater amount of omental and mesenteric adipose tissue were localized in hernial sac. Radiography of gastroduodenum showed: entry of the esophagus into the cardia was in the level of the right main bronchus. Stomach was mainly located in the chest (cardia, upper corpus half - to the level of the right main bronchus). Operation was indicated. First, we made right thoracotomy and the hernia sac was separated from the right lung and then we performed median laparotomy and the contents of the hernia sac were returned to the abdominal cavity; diaphragm defect was reconstructed with prolen mesh. Conclusion. We presented a rare case of right sided Bochdalek hernia which was discovered at late age and surgically treated with success.